Represente geometricamente o produto (x-a)•(x-b) e depois encontre uma expressão equivalente
Soluções para a tarefa
Respondido por
1
OI SaHinalinha
(x - a)*(x - b) = x² - ax - bx + ab = x² - (a + b)x + ab
exemplo
(x - 2)*(x - 3) = x² - 5x + 6
gráfico
(x - a)*(x - b) = x² - ax - bx + ab = x² - (a + b)x + ab
exemplo
(x - 2)*(x - 3) = x² - 5x + 6
gráfico
Anexos:
![](https://pt-static.z-dn.net/files/d34/e9c3419be6ccf4b06ea3564d20856783.png)
Perguntas interessantes
História,
1 ano atrás
Geografia,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Filosofia,
1 ano atrás